Case Report of acupotomy release combined with manual release under anesthesia for adhesions after unilateral total knee arthroplasty in a patient with hemophilia A - Wang, Wei; Xu, Xiaochan; Sun, Kui; Wang, Tianyao; Yang, Yonghui; Wu, Sanbing (Frontiers in Surgery, 2025)
Patients with end-stage hemophilia often require total knee arthroplasty (TKA); however, the incidence of postoperative joint adhesions in these patients is significantly higher than that in the general population. Furthermore, due to their abnormal coagulation function, the bleeding risk associated with traditional open adhesiolysis is also higher in this patient cohort compared with the general population, and conservative rehabilitation therapy yields suboptimal outcomes. Thus, there is an urgent clinical need for a safe and effective intervention regimen. This study reports a 25-year-old male patient with severe hemophilia A (factor Ⅷ deficiency), whose baseline factor Ⅷ activity was 0.8%. Severe knee joint adhesions occurred 3 months after TKA, manifested as difficulty in walking, sitting, and standing. A combined treatment regimen of “perioperative precise coagulation factor replacement + ultrasound-guided acupotomy release under anesthesia + graded manual release” was adopted for the intervention of post-TKA adhesions in patients with severe hemophilia A. The results showed that this combined regimen could achieve precise release while reducing the risk of bleeding, significantly improve joint function, and provide a new diagnostic and therapeutic strategy for the clinical treatment of such diseases.